A Comparative Prospective on the Individualization of Criminal Sentencing - Rokaj, Iv; Konini, Ivas (PRAWO i WIĘŹ, 2025)
The purpose of this paper is intended to make a theoretical and practical analysis of mitigating and aggravating circumstances in criminal law, their importance in relation to the principle of individualization of punishment as well as their importance in relation to determining the right criminal sentencing. This analysis is based on a mixed methodology, including descriptive, analytical and comparative methods by using doctrines, legislation and practice of Albanian and foreign courts as a source of data. The paper also aims to highlight the real problems related to the understanding of the theoretical importance of mitigating and aggravating circumstances and also their implementation by the Albanian courts. The main focus is on proposing a practical and unified solution to the applicability of these circumstances, taking the lead from foreign jurisdictions, primarely based on common law systems. Specifically, this paper proposes the creation of a unified methodology for the practical implementation of mitigating and aggravating circumstances in the Albanian legislation as a guide for the Albanian courts.